Factors Affecting Young Indonesian’s Intention to Purchase Counterfeit Luxury Goods - Fenitra, Rakotoarisoa Maminirina; Haryanto, Budhi (JDM (Jurnal Dinamika Manajemen), 2019)
The purpose of this study is to analyze the factors that influence consumer attitudes towards counterfeit luxury goods and their influence on intentions to buy fake luxury goods in Indonesia. Research provides better insight and understanding of consumer behavior towards counterfeit luxury goods. The sample in this study were 286 people who intended to buy fake luxury goods. Data was collected through a survey questionnaire and, analyzed by regression analysis techniques. The research findings identify that brand image, quality and price positively influence consumer attitudes towards fake luxury goods. This is because these variables are considered to have influenced individual attitudes. They have a positive attitude towards fake luxury goods in terms of brand image, price and quality and that consumer attitude is a significant variable in shaping consumer purchase intentions, because positive attitude is a stimulus for consumer purchase intention which is a predictor. consumer buying behavior; so the higher the attitude of consumers, the higher their intention to buy. These findings can be an asset for policy makers and producers of original products to formulate strategies to overcome counterfeiting activities.